Suicide: A Study of the Tafsīr - Silkaitis, Emily (Der Islam, 2022)
This article examines the tafsīr on the Qurʾānic verses pertaining to suicide, qatl al-nafs . The majority of exegetical discussions on suicide center on Moses and originate from his command to the Banū Isrāʾīl in Q 2:54, uqtulū anfusakum , which can be interpreted as "kill yourselves" or "kill one another." On the basis of etymology and historical context, commentators associate this passage with Q 4:29 and 4:66. Another such passage, Q 2:84, which outlaws bloodshed, is also associated with the Banū Isrāʾīl, in a different context. Adding Q 18:6 and Q 2:195 to the list of verses under consideration, this article traces interpretations of self-destruction from early works of tafsīr down to the late fourteenth century. Though the Qurʾānic attitude toward suicide is notoriously ambiguous, by examining the various grammatical constructions and interpretations given to these verses, one is able to establish trends and motivations in exegesis. The discussions of suicide, and condemnations where appropriate, focus on the motivation and intention of the individual rather than the act itself. Obedience to God, the nature of his commands, and the well-being of the community of believers also emerge as some of the key ethical issues in the commentaries.